Pemeriksaan Kesehatan dan Edukasi Diet Pada Penderita Diabetes Mellitus dan Hipertensi - Bitcar; Fitriyani Nasution; Halimah Tusya’diah (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Health checks are important to do, health checks in the form of vital signs and blood sugar levels are the first step in screening or early detection of various body problems, such as hypertension and diabetes mellitus. Hypertension and diabetes mellitus are non-communicable diseases that increase every year in terms of morbidity and mortality. The purpose of this activity is to carry out health checks and provide diet education for people with diabetes mellitus and hypertension. The implementation method is in the form of health checks consisting of vital signs and additional examinations such as blood sugar levels. The target of the activity is the community, especially those around the Binaraga Rantauprapat Field environment, evaluation in the form of vital signs and blood sugar levels. The results of the activity showed that several respondents were detected as suffering from hypertension and diabetes mellitus. Patients who were detected have been given education related to hypertension and diabetes mellitus diets. It is hoped that this activity will become a routine activity that is carried out, so that more and more people are detected and given prevention education related to hypertension and diabetes mellitus.